Effect of Different Organic Manures on the Growth, Yield, and Quality of Radish in Inner Terai, Nepal - Bhatta, Dinesh; Moktan, Rachana; Sapkota, Saroj; Karkee, Suraj Singh (Journal of Agriculture and Forestry University, 2026)
A field experiment was conducted from December 2021 to February 2022 at Marin Rural Municipality, Sindhuli, Nepal to evaluate the effect of various organic manures on growth, yield, and quality of radish (Raphanus sativus L.) cv. ‘Mino Early’. The experiment was laid out in a Randomized Complete Block Design with seven treatments and three replications. Organic manures (farmyard manure, poultry manure, pig manure, vermicompost, mustard oil cake and packaged organic manure) were applied on a nitrogen-equivalent basis to ensure uniform nutrient supply across treatments along with control. Data were collected on growth parameters, yield parameters, quality parameters, weed density were analyzed using ANOVA. The results revealed significant variation among the treatments. Poultry manure significantly (p≤0.05) improved most parameters: it produced the earliest germination (6.0 days), the highest leaf length at 40 DAS (26.17cm), the maximum root length (31.08 cm) and root diameter (3.06 cm), the greatest fresh root weight per plant (148.2 g) and the highest net plot yield (8.97 kg/ plot). Poultry manure also gave the largest portion of marketable roots (80.25%), the lowest forked roots (19.75%), highest total soluble solids (5°Brix), and the greatest weed suppression efficiency (65.3%) due to rapid canopy development. Mustard oil cake ranked second for several traits. In contrast, control plots recorded the lowest growth and yield parameters. Soil analysis after harvest showed that poultry manure increased soil organic matter to 2.45%, total Nitrogen to 0.13 %, available P to 68.4 kg/ha, and available K to 178.6 kg/ha, the highest among treatments. The findings of this study concluded that poultry manure is an efficient organic nutrient supplement for enhancing radish productivity and quality in the Inner Terai region of Nepal.